Association of Fok 1 (Rs10735810) Gene Polymorphism with Dental Caries in Pakistani Adolescents - Karim, Bilal; Rahim, Amena; Afzal, Muhammad; Ashfaq, Sidra; Javed, Muhammad Fahad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association of single nucleotide polymorphism of vitamin D receptor gene Fok 1 (rs10735810) with dental caries in Pakistani adolescents.Study Design: Case-control study.Place and Duration of Study: Biochemistry Department, Islamic International Medical College, Rawalpindi in cooperation with Pathology Department, Railway General Hospital, Rawalpindi Pakistan, from Sep 2019 to Aug 2020.Methodology: A total of 304 participants were included in the study. There were 152 dental caries cases and 152 normal agematched controls. After taking written informed consent, blood samples were collected from each participant. DNA extraction was done by Chelex Method. PCR was carried out to determine the respective allelic frequencies of Fok 1 (rs10735810) genotype using specific primers.Results: Out of 304 study participants, there were 26 males (17.1%) and 126 females (82.9%) in case-group; and 37 males (24.3%) and 115 females (75.7%) in control-group. No significant association of Fok 1 (rs10735810) genotype with DMFT score was found in dental caries case-group. Regarding genotypic and allelic frequencies, there was no significant association of Fok 1 (rs10735810) genotype with dental caries case-group.Conclusion: Single nucleotide polymorphism of vitamin D receptor gene Fok 1 (rs10735810) is not associated with dental caries in Pakistani adolescents.